Food habits and patterns of the Multiracial Population of Cape Town - Mannhardt, S (Department of Human Biology, 2020)
Dietitians and nutritionists today realise the importance of knowing about peoples' food habits and patterns to be able to understand their dietary and medical problems more readily. It is my intention to study the current and traditional food habits and patterns of the various population groups by interviewing as many members of each group as possible on: - daily eating patterns - cooking methods - traditional foods - taboos, feasts and fasts In the introduction the discussion will focus on the origin of food habits and patterns and the influencing factors in a wider context.